2017
DOI: 10.5898/jhri.6.3.li
|View full text |Cite
|
Sign up to set email alerts
|

Touching a Mechanical Body: Tactile Contact With Body Parts of a Humanoid Robot Is Physiologically Arousing

Abstract: A large literature describes the use of robots' physical bodies to support communication with people. Touch is a natural channel for physical interaction, yet it is not understood how principles of interpersonal touch might carry over to a robot. Exploring how interpersonal rules surrounding body accessibility and touch apply to a robot is critical toward understanding the extent to which people treat the act of touching body regions as a sign of closeness-even if the body belongs to a robotand is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 40 publications
2
40
1
Order By: Relevance
“…The observed effects in this study will likely be stronger if participants interacted with real human participants and higher fidelity of the appearance, voice, behavior, agency, and intentionality of virtual agents (Brainbridge, Hart, Kim, & Scassellati, 2011; de Melo, Gratch, & Carnevale, 2014; Fox et al, 2014; Gray, Gray, & Wegner, 2007; Hancock et al, 2011; Lucas et al, 2014; Muralidharan, de Visser, & Parasuraman, 2014; van den Brule, Dotsch, Bijlstra, Wigboldus, & Haselager, 2014). While some have argued that the mere situational presentation of an agent is sufficient to elicit social responses towards a computer (Nass & Moon, 2000; Nass et al, 1994; Reeves & Nass, 1996), others have shown strong physiological responses with more high-fidelity embodied agents such as robots (Li, Ju, & Reeves, 2016). Future research should examine whether oxytocin interacts with the fidelity of the agent.…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects in this study will likely be stronger if participants interacted with real human participants and higher fidelity of the appearance, voice, behavior, agency, and intentionality of virtual agents (Brainbridge, Hart, Kim, & Scassellati, 2011; de Melo, Gratch, & Carnevale, 2014; Fox et al, 2014; Gray, Gray, & Wegner, 2007; Hancock et al, 2011; Lucas et al, 2014; Muralidharan, de Visser, & Parasuraman, 2014; van den Brule, Dotsch, Bijlstra, Wigboldus, & Haselager, 2014). While some have argued that the mere situational presentation of an agent is sufficient to elicit social responses towards a computer (Nass & Moon, 2000; Nass et al, 1994; Reeves & Nass, 1996), others have shown strong physiological responses with more high-fidelity embodied agents such as robots (Li, Ju, & Reeves, 2016). Future research should examine whether oxytocin interacts with the fidelity of the agent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not discuss this in particular, it can be assumed that the increased arousal cannot be compared to sexual arousal, as the humanoid NAO is 57.3 cm/22.6" tall, made of white plastic, and is sometimes even described as being cute in a childlike way [30,31]. Nevertheless, their finding is important, as it shows that touching even remotely human-shaped robots evokes arousal.…”
Section: Media Equationmentioning
confidence: 99%
“…The effect of this so-called Media Equation (media equals real life) has also already been shown with regard to robots (e.g., experiencing empathy, keeping interpersonal distance) [28,29]. In terms of intimate interactions with robots, Li et al conducted a study in which the humanoid robot NAO told the participants to either touch or point to different body parts (with low and high accessibility) [30]. The results showed that people experienced an increased physiological arousal and an increased reaction time when touching regions of the robot's body with lower accessibility (e.g., buttocks or genitals).…”
Section: Media Equationmentioning
confidence: 99%
“…In Li, J., Ju, W. and Reeves, B. [13], there was a similar study, where they measure the physiological responses to arrive at a conclusion that participants have shown a considerable higher response when touching more low accessibility areas of a robot. They statistically measured the response time, deciding that the response time correlated with arousal, and the results showed that response time is higher for low accessibility areas of robots body.…”
Section: Study 2 -mentioning
confidence: 99%
“…Although the premise of this study raised issues, the moral and cultural perspective strongly decide on the human-robot relationship. When the academic community measured in on the role of a robot companion [11], the human experience of psychological intimacy with robots through the physical intimacy [12], human physiological response to intimately touching a robot [13], a systematic survey of the acceptance of sex robots [14] and aspects that influence the purchase of sex robots [15] are (to name a very few) contributing to a greater discussion that would contain what could be described as an emerging phenomena. It is important to emphasize that greater contribution in terms of assessment of social impact and risk management are required for a robust coexistence in future.…”
Section: Introductionmentioning
confidence: 99%